Genetic parameters and trends for litter size in Markhoz goats - Abdoli, Ramin; Zamani, Pouya; Mirhoseini, Seyed Ziaeddin; Hossein-Zadeh, Navid Ghavi; Almasi, Mohamad (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Prolificacy has a high economic value and is one of the most important reproduction traits in small ruminants such as Markhoz goats, which is an endangered breed. Objective: To estimate genetic, environmental and phenotypic trends, and genetic parameters for litter size (LS), as a prolificacy trait of Markhoz goat does. Methods: The study was conducted using kidding records of 3,064 Markhoz does from 1992 to 2015. Genetic parameters were estimated with a logit link function using ASReml software, fitting a repeatability animal model, with birth year, kidding year, and kidding age as fixed effects, and direct additive genetic and permanent environmental effects as random effects. Genetic, phenotypic and environmental trends were estimated by using regression of breeding value, phenotypic value and environmental deviation averages on birth year, respectively. Results: Low and negligible heritability (0.002), repeatability (0.054) and coefficient of permanent environment (0.052) were estimated for LS, which indicates low possibility to achieve rapid genetic progress through phenotypic selection. A non-significant -actually, zero- genetic trend (0.00004 heads/kidding/year), and significant negative phenotypic and environmental trends (-0.01097 and -0.01100 heads/kidding/year, respectively) were estimated in this study. Conclusion: Optimizing environmental conditions and application of high-throughput technologies in selection programs could help reducing the extinction risk of Markhoz breed.